The influence of extra load on time and force structure of vertical jump - Vaverka, V.; Jakubsova, Z.; Jandacka, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Extra load is very often used in the training for development of explosive strength. Some research works are focused on a problem of take-off activity in relationship to extra load (Nelson & Martin, 1985; Bosco et al., 1984 and others). The main aim of this study was to find how the extra load influences time and force curve of the vertical jump.